(untitled) (Vietnam Journal of Community Medicine, 2024)
Thalassemia is a hemoglobin disease caused by reduction or loss of the synthesis of one or more polypeptide chains in the globin of the hemoglobin molecule. Thalassemic patients or who had thalassemic genes are found in all provinces/cities and all ethnic groups nationwide. Investigating iron overload in Thalassemia patients is very important in providing a comprehensive view, then helping doctors more effectively treat iron chelation, contributing to improving the long-term prognosis of Thalassemia patients. Objective: To evaluate iron overload in Thalassemia patients treated at Thong Nhat General Hospital in 2023 Research method: Retrospective and prospective study, describing a series of cases, conducted on 77 Thalassemia patients at the hematology clinic and clinical hematology unit in Department of General Internal Medicine - Thong Nhat General Hospital in Dong Nai from January to June 2023. Research results: Beta Thalassemia, Beta Thalassemia HbE and Alpha Thalassemia accounted for 55.8%, 23.4% and 20.8% respectively. Iron overload accounted for 84.5%, of which severe iron overload accounted for 16.9%, while mild and moderate iron overload accounted for 67.6%. The patients responded to the iron chelator Deferiprone after 3 months of treatment with a median decrease in serum Ferritin concentration were of 68.2(-36.8 – 259.0) ng/mL. There were strong correlations between serum Ferritin and Hb, direct coombs and ALT. Conclusion: Thalassemia patients who had severe iron overload accounted for 16.9%, while mild and moderate iron overload accounted for 67.6%. The patient responded to the iron chelator Deferiprone after 3 months of treatment. There were strong correlations between serum Ferritin and Hb, Direct Coombs and ALT.